THE INFLUENCE OF PRODUCTS AND PRICES ON CONSUMER SATISFACTION OF HIJAB STALLS. ZEE50 IN PONTIANAK CITY - Sukardi; Muhammad Deva Erlangga (RADJA PUBLIKA, 2026)
The Muslim fashion industry in Indonesia is growing rapidly along with the increasing need for women to look fashionable but still in accordance with Islamic law. The city of Pontianak shows similar dynamics with the growth of local hijab businesses that are increasingly competitive, including Warung.zee50 as one of the business actors that has experienced significant development since its establishment in 2019. Warung.zee50's sales show an increasing trend from year to year, supported by innovative strategies in providing varied hijab products, affordable prices, and the utilization of digital marketing channels. Preliminary findings through observations and interviews show that product quality, material comfort, trend-following design, and pricing that suits consumer purchasing power play an important role in shaping customer satisfaction. This study aims to analyze the influence of products and prices on consumer satisfaction of Warung.zee50. The research uses a quantitative method with an associative approach. The research population is all consumers who have bought Warung.zee50 hijab products, with a total sample of 100 respondents determined through purposive sampling. Primary data was obtained through questionnaires and interviews, while secondary data came from sales documentation and social media searches. The instrument was tested using the Pearson validity test and Cronbach Alpha reliability. Data analysis included classical assumption tests, multiple linear regression, and hypothesis testing using the F test and the t test. The results of the research are expected to be able to explain the extent to which product quality and price strategy contribute to consumer satisfaction, as well as provide an empirical picture for the development of Warung.zee50's business strategy in maintaining its competitive position in the hijab fashion industry in Pontianak City.